(untitled) (Quinto Sol, 2013)
A didactic proposal addresed to history teachers working on Nivel Polimodal is posed here. We suggest the possibility to implement a work project towards the teaching and learning of socio-historic realities of Territorio Nacional de La Pampa Central in the early 20th century. We have a source available which is very valuable due to its didactic potential: the report sent by Governor Diego Gonzalez to the National Minister of Interior Dr. Rafael Castillo, concerning the journey made through the Territorio in October 1905. Advising the adoption of a narrativist approach, we propose a didactic sequence and three axis for analysis: the subjects intervening in the account, the relationship among state-civil society/ territory state-national state, and the issue of technology, especially the one concerning communications. Finally, we emphasize the importance of establishing the relationships between past and present since, in the last analysis, it is historic present the point of departure and arrival of History as well as the teaching of History.